Motul de San José : Politics, History, and Economy in a Maya Polity - Foias, Antonia E. (Book collections on Project MUSE., 2012)
Scholars have long debated the nature of Maya political organization during the Classic period (AD 250-950). Complex questions regarding political centralization, economic change, and the role of politics and economics in the rise and collapse of the civilization have been examined and reexamined from a variety of perspectives. Antonia Foias and Kitty Emery have assembled a broad collection of essays all focused on a single polity, that of Motul de San Jose. By presenting a coherent interdisciplinary body of archaeological and environmental data, the volume offers an intensely deep, focused.